Persistensi Kinerja Reksa Dana Saham di Bursa Efek Indonesia - Waelan Waelan (Jurnal Akuntansi dan Auditing Indonesia, 2009)
The purpose of this article is to analyze performance persistence of equity mutual fund in Indonesian Stock Exchange (IDX) from January 1st 2002 to December 31st 2007 by applying single factor performance model (Jensen Model) for performance measurement and Pearson correlation for persistence measurement. There are performance persistence for monthly, quarterly, semi annually, annually, every two years, and three years. Short-term performance proved a little use to predicting respective performance. Long-term performance can be useful to predicting respective performance.Keywords:    Equity mutual fund, performance persistence, Jensen model, and Pearson correlation.